Inter-relationship among nutritional quality parameters of maize (Zea mays) genotypes - Chaudhary, D P; Sapna, Sapna; Mandhania, S; Kumar, R (The Indian Journal of Agricultural Sciences, 2012)
The present study was taken up to understand the inter-relationship among various nutritional components of maize (Zea mays L.) kernel. For this purpose, 23 elite maize genotypes received from different centres of All India Coordinated Research Projects on Maize during 2009 and 2010 were used. The samples were ground to powder and processed for the estimation of various nutritional quality parameters such as protein quality, starch, oil and carotenoids and the data was correlated to find the interrelationship between these components. The results showed that the protein content exhibited a significant negative correlation with two important essential amino acids such as tryptophan and lysine. An inverse correlation was found between starch and oil indicating that breeding for high oil maize may lead to lower grain yield. A significant positive correlation was observed between oil content and 100-kernel weight postulating that although increase in oil down-regulate the starch content, the total grain yield, however, would remain unaffected. Protein content showed a non-significant negative correlation with 100-kernel weight. A significant positive correlation was noticed between protein and starch. Another important finding of this study is the positive correlation observed between oil and fat soluble total carotenoids. Breeding for high oil, therefore, would have the added advantage of biofortification of maize. The findings will help to develop improved maize having an answer to better nutrition.